PPP2R3C gene variants cause syndromic 46,XY gonadal dysgenesis and impaired spermatogenesis in humans - (:unkn) unknown (BIOSCIENTIFICA LTD, 2019)
Context: Most of the knowledge on the factors involved in human sexual development stems from studies of rare cases with disorders of sex development. Here, we have described a novel 46, XY complete gonadal dysgenesis syndrome caused by homozygous variants in PPP2R3C gene. This gene encodes B '' gamma regulatory subunit of the protein phosphatase 2A (PP2A), which is a serine/threonine phosphatase involved in the phospho-regulation processes of most mammalian cell types. PPP2R3C gene is most abundantly expressed in testis in humans, while its function was hitherto unknown. Patients and methods: Four girls from four unrelated families with 46, XY complete gonadal dysgenesis were studied using exome or Sanger sequencing of PPP2R3C gene. In total, four patients and their heterozygous parents were investigated for clinical, laboratory, immunohistochemical and molecular characteristics. Results: We have identified three different homozygous PPP2R3C variants, c.308T>C (p.L103P), c.578T>C (p.L193S) and c.1049T>C (p.F350S), in four girls with 46, XY complete gonadal dysgenesis. Patients also manifested a unique syndrome of extragonadal anomalies, including typical facial gestalt, low birth weight, myopathy, rod and cone dystrophy, anal atresia, omphalocele, sensorineural hearing loss, dry and scaly skin, skeletal abnormalities, renal agenesis and neuromotor delay. We have shown a decreased SOX9-Phospho protein expression in the dysgenetic gonads of the patients with homozygous PPP2R3C variants suggesting impaired SOX9 signaling in the pathogenesis of gonadal dysgenesis. Heterozygous males presented with abnormal sperm morphology and impaired fertility. Conclusion: Our findings suggest that PPP2R3C protein is involved in the ontogeny of multiple organs, especially critical for testis development and spermatogenesis. PPPR3C provides insight into pathophysiology, as well as emerging as a potential therapeutic target for male infertility.
Keywords: PROTEIN PHOSPHATASE 2A; MICROTUBULE-ASSOCIATED PROTEIN; SUBUNIT; PHOSPHORYLATION; TAU; EXPRESSION; DISORDERS; SOX9; G5PR